Diffractive tunable lens for remote focusing in high-NA optical systems - Bawart, Martin; May, Molly A.; Öttl, Thomas; Roider, Clemens; Bernet, Stefan; Schmidt, Michael; Ritsch-Marte, Monika; Jesacher, Alexander (Optics Express, 2020)
Remote focusing means to translate the focus position of an imaging system along the optical axis without moving the objective lens. The concept gains increasing importance as it allows for quick 3D focus steering in scanning microscopes, leaves the sample region unperturbed and is compatible with conjugated adaptive optics. Here we present a novel remote focusing approach that can be used in conjunction with high numerical aperture optics. Our method is based on a pair of diffractive elements, which jointly act as a tunable auxiliary lens. By changing the mutual rotation angle between the two elements, we demonstrate an axial translation of the focal spot produced by a NA = 0.95 air objective (corresponding to NA = 1.44 for an oil immersion lens) over more than 140 µm with largely maintained focus quality. We experimentally show that for the task of focus shifting, the wavefront produced by the high-NA design is superior to those produced by a parabolic lens design or a regular achromatic lens doublet.<br